The Älgliden Ni-Cu-Au deposit: magmatic sulfides in a subduction setting - Cordier, Carole; Coin, Kevin; Arndt, Nicholas T.; Cartigny, Pierre (Mineralium Deposita, 2019)
International audience The origin of most major sulfide Ni-Cu deposits is attributed to the segregation of immiscible sulfide liquids from intraplate silicate melts, in response to assimilation of siliceous or sulfur-bearing rocks. The Älgliden gabbroic dike in the Skellefte district (Sweden) contains Ni-Cu sulfide mineralization that is atypical because it formed in an arc setting and has a high Au content and low Ni/Cu ratio. This association led previously to a model in which the mineralization was linked to the assimilation of Cu-Au porphyry wall rocks. Based on new petrological, geochemical, and S isotope analyses of the dike and its wall rocks, we propose that assimilation of mineralized wall rocks was not instrumental in the formation of the deposit. Instead, we propose that the sulfides segregated during olivine crystallization from an evolved arc basalt and were injected into the dike in an olivine-rich crystal mush. This scenario explains the uniform dissemination of sulfide ores within norites, together with the high Au content and low Ni/Cu ratio of the ores. We propose that sulfide segregation from oxidized arc basalt was triggered by a decrease in the oxidation state of the melt, likely due to the cooling of the silicate melt or to the interaction with meta-sediments rich in organic matter, as proposed for other arc-related Cu-Ni sulfide deposits in Fennoscandia and elsewhere. At Älgliden, melt reduction would have occurred relatively late during magma evolution, leading to the formation of an uneconomic deposit consisting of low Ni ores and lacking massive sulfides.